Heinrich Coudenhove-Kalergi and Mitsuko Aoyama: travels, space and time at the turn of the 19th and 20th centuries - Švaříčková Slabáková, Radmila (Theatrum historiae, 2013)
The article explores travels and the ways of travelling of count Heinrich Coudenhove-Kalergi, father of the founder of pan-European movement Richard Coudenhove-Kalergi, and his wife Mitsuko Aoyama, focusing not only on their travel from Japan to Europe in 1896 but also on the necessity of their further travels in Europe, planned carefully by Heinrich, with the aim to educate Mitsuko.